Diy-City and internet of things. A research hypothesis around interactive urban design - Marco Trisciuoglio (Agathón)
In a renewed and critical interpretation of the idea of the so-called ‘smart city’, it may serve to prefigure a paradigm shift in urban design: from the apparently irresolvable opposition between top-down and bottom-up processes that marked the debates on participatory design in the last quarter of the 20th century, it will be possible to move towards the idea of collaboration between citizens, businesses and institutions that is both top-down and bottom-up. The tools offered by digital technologies can in fact promise a horizon of ‘co-making’, understood as an interactive urban project, capable of refining the production of the city space, but also of expressing its social and symbolic value and finally of conceiving and designing innovative urban scenarios in a more participatory way. In order to do this, the research hypothesis illustrated prefigures a sort of Turing machine of urban design, capable of transforming data (voluntarily and involuntarily provided by citizens) into actions aimed at designing the space of the city.